Quantifying upper limb motor impairment in people with Parkinson’s disease: a physiological profiling approach - Lewis A. Ingram; Vincent K. Carroll; Annie A. Butler; Matthew A. Brodie; Simon C. Gandevia; Stephen R. Lord (PeerJ, 2021)
Background Upper limb motor impairments, such as slowness of movement and difficulties executing sequential tasks, are common in people with Parkinson’s disease (PD). Objective To evaluate the validity of the upper limb Physiological Profile Assessment (PPA) as a standard clinical assessment battery in people with PD, by determining whether the tests, which encompass muscle strength, dexterity, arm stability, position sense, skin sensation and bimanual coordination can (a) distinguish people with PD from healthy controls, (b) detect differences in upper limb test domains between “off” and “on” anti-Parkinson medication states and (c) correlate with a validated measure of upper limb function. Methods Thirty-four participants with PD and 68 healthy controls completed the upper limb PPA tests within a single session. Results People with PD exhibited impaired performance across most test domains. Based on validity, reliability and feasibility, six tests (handgrip strength, finger-press reaction time, 9-hole peg test, bimanual pole test, arm stability, and shirt buttoning) were identified as key tests for the assessment of upper limb function in people with PD. Conclusions The upper limb PPA provides a valid, quick and simple means of quantifying specific upper limb impairments in people with PD. These findings indicate clinical assessments should prioritise tests of muscle strength, unilateral movement and dexterity, bimanual coordination, arm stability and functional tasks in people with PD as these domains are the most commonly and significantly impaired.